Parametric Study of Magnus Wind Turbine with Spiral Fins using BEM Approach - R. Mdouki (Journal of Applied Fluid Mechanics, 2021)
The aim of this work is to carry out an aerodynamic analysis to assess the power and identify the characteristics of the horizontal axis Magnus type wind turbine with spiral fins. A parametric study is achieved to analyze the effects of the different influence parameters such as the turbine tip speed ratio, the cylinder spinning ratio, the blade aspect ratio and the cylinder hub-tip ratio. The analysis approach adopted in this study is the Blade Element Momentum BEM using the experimental lift coefficient data for the configuration of spinning cylinders with spiral fins. In this analysis, losses are not taken in consideration. Both axial and angular interference coefficients are evaluated for this type of wind turbine. The former is assessed by solving a quadratic equation and the latter is calculated from a classic formulation including the term of spinning. An iterative process is followed to achieve this task. Concerning the obtained results, the aerodynamic characteristics of the Magnus wind turbine, analyzed in this study, provide some elucidation to lead a successful preliminary design of this novel type of machine.